2018
DOI: 10.1007/s00167-018-5259-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in morphology exist in posterior condylar offsets of the knee in Korean population

Abstract: Purpose This study aimed to analyze the morphometric data from magnetic resonance images of arthritic knees in Korean adults, and to identify the existence of morphological diferences of femoral posterior condylar ofset (PCO) between genders. Methods The diferences in anthropometric PCO data in 975 patients (825 female and 150 male) were evaluated. The distances from the anterior and posterior femoral shaft cortex line to the most posterior femoral condyle tangent line were deined as the anterior-posterior dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…The morphometric characteristics are related to genetic, environmental, and sociocultural conditions and lifestyle, health, and functional status. The variation complicates providing a standard interpretation of their respective values [20]. Therefore, this study is aimed at evaluating the patellar-position difference between the genders by using the Insall-Salvati ratio and MRI.…”
Section: Introductionmentioning
confidence: 99%
“…The morphometric characteristics are related to genetic, environmental, and sociocultural conditions and lifestyle, health, and functional status. The variation complicates providing a standard interpretation of their respective values [20]. Therefore, this study is aimed at evaluating the patellar-position difference between the genders by using the Insall-Salvati ratio and MRI.…”
Section: Introductionmentioning
confidence: 99%
“…6). Recently, a three-dimensional morphology study showed a gender difference for femoral posterior condylar offset and condylar height for the femoral trochlea in the Korean population (Koh et al, 2019b;Koh et al, 2019c). This study provides guidelines for the design of a suitable femoral component for TKA considering gender-specific differences in the Korean population (Koh, Nam, Chung, Kim, Chun and Kang, 2019b;Koh, Nam, Chung, Lee, Kim, Kim and Kang, 2019c).…”
Section: Fig 5 Schematic Of a Subject-specific Musculoskeletal Modelmentioning
confidence: 75%
“…Since women's knees show mediolaterally narrow and trapezoidal axial shapes [11,[20][21][22] and the orientation of the trochlear groove is also different from that of men's knees [41], there is a difference in orientation of the axes using bony landmarks. In addition, the sagittal curvature diameters [36] and posterior condylar offset [18,42], which are thought to have an effect on KAA, show a disparity between men and women. Therefore, if the same angular reference is applied in TKA, the anatomical diversity between men and women would be ignored.…”
Section: Discussionmentioning
confidence: 99%